The Pedestrianisation and Its Relation with Enhancing Walkability in Urban Spaces - Najmaldin Hussein (Journal of Contemporary Urban Affairs, 2018)
The study aimed to answer the question of how pedestrianisation can influence walkability to increase physical activity vitality and livability of urban spaces. Therefore, after the theoretical understanding of the framework of the research, the study will focus on experimental research on the Salamis rode of Famagusta to assess the problems of walkability in the street to propose a sustainable and human-friendly solution for this area. The main aim of the research is to find what is the interrelation between pedestrianisation in public urban spaces and walkability? Therefore, it concludes that walkability as a part of the pedestrianisation scheme will lead to an increase in the quality of the urban environment by increasing safety and organization in urban infra-instructors.